Spirituality in counselling : assisting counsellors and the depressed : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy, in Social Policy and Social Work at Massey University - Stewart, Bruce William (Massey University, 1999)
This study qualitatively explored the views of six people who use spirituality in their counselling work with the depressed. These findings were compared to the counselling literature on spirituality and a theoretical framework developed for this research. There are indications that spirituality in counselling is helpful in alleviating depression, as seen through the literature and through the reports from participants. However, this was more strongly supported in the literature than with the participants. Empowerment, belonging and universal sacredness emerged as helpful conceptualisations for counsellors who wish to incorporate spirituality in their work with depressed clients. In addition, spirituality assisted the counsellors personally and enhanced their practice. Increased counsellor awareness of their spiritual beliefs and values in counselling was found beneficial to counsellors working with depressed clients. This helps counsellors to become less vulnerable to imposing their views on the client, which can reduce their ability to help. The research demonstrated that a healthy spirituality might reduce vulnerability to depression while conditions that create vulnerability to depression may also reduce spirituality's capacity to enhance meaning and purpose in life. The depressed also suffer from powerlessness, isolation, and devaluation that can be alleviated through spirituality in counselling. This study further identified that in certain circumstances spirituality was not helpful and that some barriers existed for counsellors in using it in their work. On balance, the study found encouragement to integrate spirituality into counselling work for depression.
Keywords: Counseling; Psychology; Religion